PENGARUH DPK, ROA, CAR, NPL, DAN JUMLAH SBI TERHADAP PENYALURAN KREDIT PERBANKAN (Studi Pada Bank Umum Go Public di Indonesia Periode 2008-2011) - Oktaviani, Oktaviani; Rini Demi Pangestuti, Irene (Faculty of Economics and Business Diponegoro University, 2012)
Credit is one way to develop the economic of our country. Commercial bank can get more revenue from interest income from lending. This research aims to analyze influence of variables Third Party of Fund (DPK), Return On Assets (ROA), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), and Certificate of Bank Indonesia (SBI) toward of amount banking credit. The number of samples in this study are 22 Commercial Bank uses purposive sampling method. It is a method to found sample with various measurement. All the sample are companies that listed in Indonesia Stock Exchange for period 2008 to 2011 which apply polled data method and collects data are about 88 data observation. Data analysis that used in this study are multiple regression liniear and assumption classic tests which consist of normality test, multicolieniarity test, autocorrelation test and heterocedasticity test. Hypotesis testing uses F-test and t- test. Based on the result of analysis shows independent variables (Third Party of Fund (DPK), Return On Assets (ROA), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), and Certificate of Bank Indonesia (SBI)) simultanieously effect Credit of Banking. Whereas partially, Third Party of Fund (DPK) and Capital Adequacy Ratio (CAR) have positive and significant impact on Credit of Banking. In Other Hand, Certificate of Bank Indonesia Â (SBI) has negative and significant impact on Credit of Banking. At Last, Return On Assets (ROA) and Non Performing Loan (NPL) have positive and insignificant influence to Credit of Banking. The value of adjusted R square is 0,978 and it means independent variables can explain the dependent variable as much as 97,8%, while the remaining amount of 2,2% is influenced by other factors which not included in the model.